Tolerance Between Religions in Jungjang Village, Arjawinangun District, Cirebon - Aziz Maulana; Suwarma Al Muchtar (Department of Civic Education, 2021)
Indonesia, which is a multicultural nation, will not be separated from the rampant cases of intolerance between religious communities that lead to religious blasphemy, clashes between religious communities and even the destruction of houses of worship that harm many people and cause chaos in society. To deal with this, it is necessary to strengthen understanding of inter-religious tolerance which aims to increase public understanding of the importance of maintaining national unity, since in principle every religion teaches goodness to its people. Therefore, in realizing tolerance between religious communities, it can be done through good communication between religious leaders, a culture of harmony and mutual respect for differences as well as helping fellow humanity towards other religions. This study uses a qualitative approach with a descriptive method, with data collection using interviews, observation and documentation. The results of this study indicate that the people of Jungjang village, Arjawinangun district, Cirebon have a very good culture of tolerance and are able to create a peaceful atmosphere in the community even though there are houses of worship nearby the location.